2020
DOI: 10.1074/jbc.ra120.013175
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cι promotes UBF1–ECT2 binding on ribosomal DNA to drive rRNA synthesis and transformed growth of non-small-cell lung cancer cells

Abstract: Epithelial cell–transforming sequence 2 (ECT2) is a guanine nucleotide exchange factor for Rho GTPases that is overexpressed in many cancers and involved in signal transduction pathways that promote cancer cell proliferation, invasion, and tumorigenesis. Recently, we demonstrated that a significant pool of ECT2 localizes to the nucleolus of non-small-cell lung cancer (NSCLC) cells, where it binds the transcription factor upstream binding factor 1 (UBF1) on the promoter regions of ribosomal DNA (rDNA) and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…For example, PKC-mediated phosphorylation of cytoplasmic Ect2 on Thr328 within the autoinhibitory linker led to activation of the oncogenic Rac1-Pak-Mek1,2-Erk1,2 pathway and PKC-mediated phosphorylation of nuclear Ect2 stimulated Rac1-dependent ribosomal DNA (rDNA) transcription. (Justilien et al, 2017;Justilien and Fields, 2009;Justilien et al, 2011;Justilien et al, 2020). Similarly, Ect2 mislocalization association has been reported in ovarian and colorectal cancers (Cook et al, 2022;Huff et al, 2013).…”
Section: Epithelial Cell Transforming Sequence 2 (Ect2)mentioning
confidence: 59%
“…For example, PKC-mediated phosphorylation of cytoplasmic Ect2 on Thr328 within the autoinhibitory linker led to activation of the oncogenic Rac1-Pak-Mek1,2-Erk1,2 pathway and PKC-mediated phosphorylation of nuclear Ect2 stimulated Rac1-dependent ribosomal DNA (rDNA) transcription. (Justilien et al, 2017;Justilien and Fields, 2009;Justilien et al, 2011;Justilien et al, 2020). Similarly, Ect2 mislocalization association has been reported in ovarian and colorectal cancers (Cook et al, 2022;Huff et al, 2013).…”
Section: Epithelial Cell Transforming Sequence 2 (Ect2)mentioning
confidence: 59%
“…Increasing evidence, including our previous study, indicates that dysregulated ECT2 activity is implicated in many types of cancer and that ECT2 depletion suppresses tumorigenesis ( 35 , 41 , 52 , 53 ). These findings suggest that ECT2 acts as an oncogenic protein.…”
Section: Discussionmentioning
confidence: 81%
“…Contrary to this finding, most of the studies reported ECT2 as a marker of bad prognosis in solid malignancies. 11,25 Despite many molecular updates for ovarian carcinomas in the literature, still the overall survival of the patients is poor worldwide while it is graves in our part of the world. Copy number variations are lately been emphasized for their role in potential prognostication of SOC patients in different studies.…”
Section: Discussionmentioning
confidence: 99%